1985
DOI: 10.1111/j.1365-2494.1985.tb01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary feeding of forage to grazing dairy cows

Abstract: Grass silage was offered to continuously stocked dairy cows in two experiments. In the first 12 weeks of the grazing season (Experiment 1) 32 cows were offered grazed herbage only (G), or grazed herbage with a silage supplement offered for 45 min after morning milking (GMS), over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 11 publications
3
36
1
Order By: Relevance
“…Furthermore, the rumination time of the 2 3 3SH animals was 17% longer than all other treatments (428 min). Phillips and Leaver (1985) reported that the replacement of herbage with silage led to increased rumination times, owing to an increase in fibre intake. This is confirmed in this study when the NDF intakes are considered, as the 2 3 3SH had a 0.24 higher NDF intake than the treatments that were not supplemented with silage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rumination time of the 2 3 3SH animals was 17% longer than all other treatments (428 min). Phillips and Leaver (1985) reported that the replacement of herbage with silage led to increased rumination times, owing to an increase in fibre intake. This is confirmed in this study when the NDF intakes are considered, as the 2 3 3SH had a 0.24 higher NDF intake than the treatments that were not supplemented with silage.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of these practices is to minimise or eliminate poaching damage. Nevertheless, there is abundant evidence that supplementation with grass silage has negative effects on milk protein concentration (Phillips and Leaver, 1985) and that the milk yield response can range from 20.75 to 11.1 kg milk/kg forage supplement DM depending on the availability of pasture (Phillips, 1988). Allocating animals' limited access to pasture for a few hours per day has previously been shown to increase milk production and milk protein concentration when compared with cows housed on a full-time basis (Dillon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, the increase of pasture allowance resulted in a total increase of grazing time of 112 min day -1 , a decrease of the bite rate of 8 bites min -1 and an increase of the total food intake (Table 3). The use of supplementary preserved forages such as grass silage can be used to increase the total DM intake, when offered for a short period each day as a buffer feed for grazing dairy cows fed in low-mass pasture (Phillips and Leaver 1985). However, the response depends on pasture availability, the relative nutritive values of grazed herbage and supplementary forage, and the time of access to each feed (Hernandez-Mendo and Leaver 2004, PerezPrieto et al 2011).…”
Section: Milk Production and Animal Performancementioning
confidence: 99%
“…On the other hand, the silage may have limited the intake of pasture. Therefore, silage was given additionally to act as a buffer, to ensure the animals would be provided with sufficient amounts of DM (Phillips and Leaver 1985). Table 4.…”
Section: Milk Production and Animal Performancementioning
confidence: 99%
See 1 more Smart Citation